Keramba Jaring Apung SMART sebagai Inovasi Sistem Budidaya Ramah Lingkungan di Perairan Danau dan Waduk - Andri Warsa; Lismining Pujiyani Astuti (Jurnal Teknologi Lingkungan, 2022)
Aquaculture activity using floating net cage (FNC) in lake or reservoir was rapidly developing, and it was over carrying capacity. Uneaten feed and fish metabolisms were caused by water quality degradation. Some innovation was needed to diminish pollutant loading for cultivation activity, and SMART FCN can do it. SMART FNC is a water management system with circulation and aquatic plants as an innovation for conventional KJA. This paper aimed to shown SMART FCN construction as an eco-friendly cultivation system and estimate organic matter and phosphorus pollutant loading reduced by SMART FCN. The research was done at Cirata Reservoir in October–December 2019. The research using FCN with size 6x6 m with depth 4.5 m. The nile tilapia (Oreochromis niloticus) seed used was 15 kg with an average weight is 22.5 g/ind or with a density 7 ind/m3 or 775 fish total. It was feeding as much as 5% of the fish weight and three times per day. The average fish growth rate is 1.6 g/day with a food conversion ratio is 1.41, with a harvest biomass is 104.0 kg. FCR decreasing can reduce organic matter (OM) and total phosphorus for each ton of fish by 200 kg OM and 50.8 kg P, respectively. The filtration effectiveness of water spinach to decreasing P-PO4, BOT, NO2, and N-NO3 were 33.2, 31.2, 31.0, and 40.3%, respectively.